Teacher Classroom Management Skills and Its Implementation in Primary School Learning - Zainuddin, Zainuddin; Hardiansyah, Framz (Mimbar Sekolah Dasar, 2023)
The teachers’ skills to manage a class are an effort to attain students' competence in learning participation. This research aims at analyzing the teachers’ skills to manage a classroom and describing their implementation in the learning process. It employs qualitative research method by using interview, observation, and questionnaire techniques to collect the data. The analyzed data analysis were collected, reduced, and concluded. The data validity was done by conducting source triangulation and technique triangulation. Source triangulation is used to trial the credibility of the data by checking it against data from various sources. In addition, technique triangulation is used to test the data's credibility by using different techniques on the same source. The findings showed that the classroom teachers could fairly manage their classes in accordance with classroom management principles. The teachers displayed a warm and enthusiastic attitude. They provided challenges and reinforcement, instilled discipline, concerned about the classroom environment, designed a positive learning environment, and were able to be a good communicator. Therefore, the teachers’ skills to manage the class was classified in a good category (69.1%).